A new species of the genus Agnaptoria Reitter from Xizang, China (Coleoptera, Tenebrionidae: Blaptini) - Ren, Guo-Dong; Liu, Hao-Yu (Zootaxa, 2009)
The genus Agnaptoria Reitter (1887) from China is studied and a new species is reported, A. nigripes sp. nov. (CHINA, Xizang). The formerly unknown male of A. amdoensis Medvedev (2006) is described for the first time; also, the poorly known male of A. markama Shi & Ren (2005) is redescribed.